PEMASARAN HASIL USAHA PERHUTANAN SOSIAL (Studi Kasus Hutan Kemasyarakatan Solok Radjo, Nagari Aie Dingin, Kabupaten Solok, Sumatera Barat) (Jurnal ForestrIndo, 2024)
The formation of social forestry business groups that are evolving within the social forestry program is expected to enhance the business capacity for the well-being of farmers. This research aims to understand the management of social forestry in HKm Solok Radjo and formulate appropriate business development in HKm Solok Radjo. The method used is descriptive statistical analysis with 55 members of HKm Solok Radjo and 16 marketing institutions as respondents. The management of HKm Solok Radjo is carried out on forest products collected from the forest and cultivated plants on the HKm cultivation land. Agroforestry planting patterns are only found in coffee plants combined with Leucaena. The management carried out by farmers includes land preparation, seed procurement, planting, maintenance, harvesting, and marketing. Efficient marketing channels are characterized by shorter marketing chains, lower marketing margins, a higher farmer's share, and an evenly distributed profit-to-cost ratio. Therefore, farmers need to sell their agricultural products directly to consumers and process their products to add value.